Effect of combined exercises on mental, physical, and dribbling skills in young wheelchair basketball players - Mohammed Ali , Ahmed Amer; Oudah Al-Oudah, Aqeel Hameed (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
Wheelchair basketball is one of the sport that plays a significant role in the rehabilitation of individuals with special needs. Players must have a high degree of speed and focus their attention on different perceptual situations in the field. A total of 10 players were selected as sample from the Paralympics Subcommittee in the Babylon Province. They were randomly divided into experimental and control groups. After conducting the pre-tests, the combined exercises prepared by researchers were applied to the experimental group. These exercises were given to the experimental group in sessions of 30 minutes, three days per week. The control group followed the traditional curriculum. After conducting the post-test, the data were processed using the SPSS. The results indicated that the combined exercises positively contributed to the development of mental, physical, and dribbling skills of the wheelchair basketball players. Therefore, the authors recommend to include these combined physical exercises in the training curricula.